MEMORY AND OBLIVION: TANGIBLE IMAGES AND UTOPIA - Oosterbeek, Luiz (Design/Arts/Culture, 2023)
The thesis of W. Benjamin on the concept of History echoes as almost an anti-postmodernism manifesto: the approach to the past is structured through images, not narratives. Indeed, in the tension between history (the universal past rooted in agreed replicable methodologies for a human archetype) and memory (the ego or sociocentric past rooted in individual experiences), egos design narratives and try to fit evidence into them, whereas the historical past is constantly reconstructed through zooming in details that generate new images. The image in history, as the mental image in individuals, is not a layer of arrival, nor even a point of departure, but a vehicle of transformation of how space is perceived (as Kant argued) or constructed (following Bachelard), the phenomenological process of performing tasks in space being the driver of such construction (as argued by Ingold). The design of history through images is, in this sense, the process of social construction of cultural landscapes, i.e., of the poetics of space. This is a process that encompasses four mechanisms of change: identification (based on senses and, primarily, on touch and sound), adaptation (the Kantian perception of the space as the scenario of human aptitude), transformation (the poetics of the making, creating new landscapes by changing their core images) and method (namely the dialectics of tangible and intangible dimensions). The tension between image and narrative is, ultimately, the root of the tension between ego/socio-centered memories and the anthropic-rational history. In such a process, history builds from memories, by overcoming their narratives and preserving basic units of information that may be recombined, to create novel images of the past, but also of the present and the future. In such a process, history considers memory oblivion and an indicator of reliability or not of those memories. In this paper we discuss how material culture is the backbone of mental images and why it has a much more plastic and transformative nature than intangible narratives, which are expressions of the consolidation (and conservation) of understandings. The keyword in such a memory process is oblivion: images allow us to forget fossil narratives and to move into new utopias.